A Review of the Role of Actinobacteria as a Source of Bioactive Compounds - Kelvin , Keroro; Cromwell , Kibiti; Huxley Mae , Makonde (Multidisciplinary Journal of Technical University of Mombasa, 2025)
A systematic review of 57 peer-reviewed studies published between 2015 and 2024 was conducted to provide information on the role of Actinobacteria as a source of bioactive compounds. Study emphases included ecological distribution, metabolite diversity, research approaches, and publication trends. The reviewed papers covered soil, marine, freshwater, plant-associated, and extreme environments. Soil-derived isolates accounted for 42% of reports, followed by marine (28%), extremophilic (15%), freshwater (10%), and plant-associated (5%) strains. Streptomyces and Micromonospora were the most frequently reported genera. In terms of production of bioactive compounds, 65% of studies confirmed production of antibacterial, antifungal, anticancer, antiviral, and anti-inflammatory metabolites. 20% presented preliminary but promising results and 15% reported no significant activity. 40% of studies employed genomic-based strategies such as genome mining and metagenomics, 35% applied chemical profiling techniques, and 25% used classical isolation and culture methods. Publication trends indicated steady global growth with a peak in 2021, while African contributions represented less than 5% of studies. The most commonly reported metabolites were antibiotics, antifungals, and biosurfactants, with aminoglycosides and macrolides being the most cited classes. The findings show that Actinobacteria is a potential resource for drug discovery therefore there is need for further bioprospecting.